The Function of TIF2/GRIP1 in Mouse Reproduction Is Distinct from Those of SRC-1 and p/CIP - Gehin, Martine (American Society for Microbiology, 2002)
Human TIF2 (hTIF2) is a member of the p160 family of nuclear receptor coactivators, which includes SRC-1 and p/CIP. Although the functions of hTIF2 and of its mouse homolog (GRIP1 or mTIF2) have been clearly established in vitro, their physiological role remains elusive. Here, we have generated mice lacking mTIF2/GRIP1 and examined their phenotype with a particular emphasis on reproductive functions. TIF2(−/−) mice are viable, but the fertility of both sexes is impaired. Male hypofertility is due to defects in both spermiogenesis (teratozoospermia) and age-dependent testicular degeneration, and TIF2 expression appears to be essential for adhesion of Sertoli cells to germ cells. Female hypofertility is due to a placental hypoplasia that most probably reflects a requirement for maternal TIF2 in decidua stromal cells that face the developing placenta. We conclude that TIF2 plays a critical role in mouse reproductive functions, whereas previous reports have not revealed serious fertility impairment in SRC-1(−/−) or p/CIP(−/−) mutants. Thus, even though the three p160 coactivators exhibit strong sequence homology and similar activity in assays in vitro, they play distinct physiological roles in vivo, as their genetic eliminations result in distinct pathologies.